2019
DOI: 10.1063/1.5120719
|View full text |Cite
|
Sign up to set email alerts
|

A substantial increase of Curie temperature in a new type of diluted magnetic semiconductors via effects of chemical pressure

Abstract: Chemical pressure is an effective method to tune physical properties, particularly for diluted magnetic semiconductors (DMS) of which ferromagnetic ordering is mediated by charge carriers. Via substitution of smaller Ca for larger Sr, we introduce chemical pressure on (Sr,Na)(Cd,Mn) 2 As 2 to fabricate a new DMS material (Ca,Na)(Cd,Mn) 2 As 2 . Carriers and spins are introduced by substitutions of (Ca,Na) and (Cd,Mn) respectively. The unit cell volume reduces by 6.2% after complete substitution of Ca for Sr, s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 41 publications
1
3
0
1
Order By: Relevance
“…4(a) shows the temperature-dependent resistivity of Li 1.04 (Cd 1Àx Mn x )As samples with x = 0, 0.02, 0.04, 0.06, 0.08, 0.10, and 0.15. The resistivity of parent compound LiCdAs increases with decreasing temperature, which exhibits a typical semiconductor behavior 39 and is consistent with the previous report. 25 The resistivity of the doped samples also increases monotonically with the decrease in temperature at various doping concentrations.…”
Section: Resultssupporting
confidence: 92%
“…4(a) shows the temperature-dependent resistivity of Li 1.04 (Cd 1Àx Mn x )As samples with x = 0, 0.02, 0.04, 0.06, 0.08, 0.10, and 0.15. The resistivity of parent compound LiCdAs increases with decreasing temperature, which exhibits a typical semiconductor behavior 39 and is consistent with the previous report. 25 The resistivity of the doped samples also increases monotonically with the decrease in temperature at various doping concentrations.…”
Section: Resultssupporting
confidence: 92%
“…This is opposite to the case observed in (Ba,K)(Zn,Mn) As , where positive chemical pressure induced by P/As substitution suppress the 25 . Previous results have shown that long-range ferromagnetic interaction in many p -type DMSs is predominantly mediated by the itinerant carries 26 , 27 , 35 39 . In p -type (Ba,K)(Zn,Mn) As , the long-range magnetic ordering is mediated by the p states of As through As 4 p -Mn 3 d hybridization.…”
Section: Resultsmentioning
confidence: 99%
“…While in contrast, the resistivity of Sr-doped sample is lower than that of Ba(Zn Co ) As in most temperature range. This can be attribute to the broadened electronic bandwidth and increased carrier mobility with compression of the lattice 26 , 35 . To examine whether the type of carriers for Sr-doped samples with iso-valent doping has been changed, we measured Hall effect.…”
Section: Resultsmentioning
confidence: 99%
“…Theoretically, this probability will increase drastically with increasing x, which enhances the direct antiferromagnetic coupling interaction between Mn-Mn pairs. We notice that with this interaction, 100% Mn doped Ca(Zn 1−x Mn x ) 2 As 2 , CaMn 2 As 2 , becomes an antiferromagnet with Neel temperature ~ 62 K [34] .…”
mentioning
confidence: 84%